A TrkB receptor agonist N-acetyl serotonin provides cerebral protection after traumatic brain injury by mitigating apoptotic activation and autophagic dysfunction. (January 2020) - Rui, Tongyu; Wang, Zufeng; Li, Qianqian; Wang, Haochen; Wang, Tao; Zhang, Mingyang; Tao, Luyang; Luo, Chengliang
Abstract: Tropomyosin-related kinase B (TrkB) has emerged as a key mediator in the pathophysiology of traumatic brain injury (TBI). However, it is not known whether TrkB's agonist N-acetyl serotonin (NAS) involves in neuronal damage and brain dysfunction caused by TBI that is known as one of the most important causes of disability and death worldwide. Here, we investigated the effects of NAS on brain edema, blood-brain barrier (BBB), apoptosis activation and autophagy dysfunction after experimental TBI. A mouse TBI model was applied, NAS and ANA-12 (an antagonist of TrkB) were administered. Here, we first found that NAS administration ameliorated TBI-induced brain edema, blood-brain barrier (BBB) disruption, increase of matrix metalloproteinase-9 (MMP-9) expression and decrease of claudin-5 expression. NAS treatment decreased TBI-induced cell death and apoptosis activation (detected by propidium iodide labeling, TUNEL staining, blots for Bcl-2, Bax and caspase-3). In addition, NAS treatment decreased the expression of Beclin-1 and LC3, along with ratio of Beclin-1/Bcl-2, but increased p62 expression following TBI. NAS also enhanced the activation of the TrkB/Akt pathway following TBI. Whereas, the above protective effect of NAS following TBI was blocked by ANA-12 addition. Thus, we conclude that NAS-initiating the TrkB/Akt signaling cascade provides neuroprotection after experimental TBI in mice, which at least in part through inhibiting apoptosis activation and autophagic dysfunction. Highlights: NAS alleviated TBI-induced brain water contents and BBB disruption. NAS decreased TBI-induced cell death and apoptosis activation. NAS inhibited TBI-induced autophagy dysfunction. The protective effect of NAS post-TBI was blocked by ANA-12 addition. NAS exerted the protective effects via the TrkB/Akt pathway after TBI.